The Teacher's Efforts in Developing Student Morality - Septriana, Andri Ecu; Nuryani, Pupun (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Morality is a very important rule to be enforced in a society because it can be a sign in life as well as protection for the environment. Morality results from intellectual behavior, emotions, or the thinking of every human being which is essentially a rule in life to respect and be able to distinguish between right and wrong in society. Morality development greatly affects the environment, so that in childhood, morality education is very important to do, therefore a teacher must be able to develop the moralities of each student by doing various appropriate ways. This study aims to describe how the teacher's efforts in developing student moralities. Meanwhile, this research is qualitative research using the literature study method. Based on the literature study, the teacher's efforts in developing student moralities through assigning assignments and being collected on time students turned out to have benefits, one of which was being able to build student discipline through assignments sent on time